Effects of UV for Cycloaliphatic Epoxy Resin via Thermokinetic Models, Novel Calorimetric Technology, and Thermogravimetric Analysis. Issue 1 (December 2018) - Laiwang, Bin; Liu, Shang-Hao; Tsai, Yun-Ting; Deng, Jun; Jiang, Hui-Chun; Li, Bei; Shu, Chi-Min
Abstract The cycloaliphatic epoxy resin selected for this study was 3, 4-epoxycyclohexane methyl-3′4′-epoxycyclohexyl-carboxylate (EEC). Epoxy resin has numerous applications, such as varnishes, tires, and electronic materials. However, the extensive used of chlorofluorocarbon (CFC) compounds in the last century has resulted in the formation of a hole in the ozone layer. As a consequence, solar radiation is intensifying gradually; therefore, continuous irradiation by sunlight should be avoided. The results of solar radiation can exacerbate the deterioration and photolysis of compounds. Through thermogravimetry and differential scanning calorimetry, the apparent onset temperature of EEC and EEC was analyzed under UV radiation for different durations. Thermokinetic data were used to determine the parameters of thermal decomposition characteristics through simulation to assess the reaction of EEC and EEC under UV radiation for different durations. The goal of the study was to establish the parameters of thermal decomposition characteristics for the effects of UV on EEC, as well as the probability of severity of thermal catastrophe.